Benefit of antenatal corticosteroids by year of birth among preterm infants in Canada during 2003–2017: a population‐based cohort study. (9th October 2020) - Melamed, N; Murphy, K; Barrett, J; Asztalos, E; McDonald, SD; Yoon, EW; Shah, PS; ,
Abstract : Objective: To evaluate the changes in the associations of antenatal corticosteroids (ACS) with neonatal mortality and severe neurological injury over time (2003–17). Design: National, population‐representative, retrospective cohort study. Setting: Level III neonatal intensive care units participating in the Canadian Neonatal Network. Population: All infants born at 23 0/7 –33 6/7 weeks of gestation ( n  = 43 456). Methods: We estimated the associations between exposure to ACS and neonatal outcomes by year of birth. Year of birth was considered both continuously and categorically as three consecutive epochs. Main outcome measure: Neonatal mortality and severe neurological injury. Results: The absolute rates of neonatal mortality and severe neurological injury decreased during the study period in both the ACS and No ACS groups. For infants born at 23 0/7 –30 6/7 weeks of gestation, ACS was associated with similar reductions in neonatal mortality across the three epochs (9.0% versus 18.1%, adjusted relative risk [aRR] 0.54, 95% CI 0.47–0.61 in 2003–09; 7.6% versus 19.6%, aRR 0.51, 95% CI 0.44–0.59 in 2010–13; and 7.3% versus 14.5%, aRR 0.56, 95% CI 0.46–0.68 in 2014–17) and in severe neurological injury (13.2% versus 25.8%, aRR 0.57, 95% CI 0.50–0.64 in 2003–09; 7.4% versus 17.4%, aRR 0.53, 95% CI 0.43–0.66 in 2010–14; and 7.2% versus 14.8%, aRR 0.59, 95% CI 0.48–0.74 in 2014–17). Conclusion: Despite the ongoing improvements in neonatal care of preterm infants, as reflected by the gradual decrease in the absolute rates of neonatal mortality and severe neurological injury, the association of ACS treatment with neonatal mortality and severe neurological injury among extremely preterm infants born at 23–30 weeks of gestation has remained stable throughout the study period of 15 years. Tweetable abstract: Despite the gradual decrease in the rates of neonatal mortality and severe neurological injury, antenatal corticosteroids remain an important intervention in the current era of neonatal care. Tweetable abstract: Despite the gradual decrease in the rates of neonatal mortality and severe neurological injury, antenatal corticosteroids remain an important intervention in the current era of neonatal care.